Endocrine evaluation of hirsutism - John Mihailidis, MD; Racha Dermesropian, MD; Pamela Taxel, MD; Pooja Luthra, MD, FACE; Jane M. Grant-Kels, MD (Wolters Kluwer, 2017)
Hirsutism is defined as excessive terminal hair growth in a male pattern in females. It typically affects 5 to 10% of reproductive-age women. Excessive hair growth can often cause significant psychological and emotional distress. As a result, hirsutism is a common presenting complaint to healthcare professionals, including dermatologists, as women search for cosmetic and medical solutions to their problem. Hirsutism results from excess production of androgens, often from ovarian or adrenal sources. It is typically associated with a metabolic syndrome like polycystic ovarian syndrome (PCOS), but can be idiopathic or medication-induced. This article provides an endocrine perspective for the evaluation and management of hirsutism.